A quantitative evolved gas analysis for extra-terrestrial samples. (February 2020) - Verchovsky, A.B.; Anand, M.; Barber, S.J.; Sheridan, S.; Morgan, G.H.
Abstract: Evolved gas analysis (EGA) has been successfully applied to the studies of meteorites and Apollo lunar samples. It consists of linear heating of a material with registration of the released volatile compounds, typically using a spectrometric technique. However, so far no quantitative comparison was possible of the amount of gases released during heating of a sample. To address this limitation, we have developed a Quantitative EGA (QEGA) technique using our custom-built Finesse mass spectrometry system. It is based on calibration of the quadrupole mass spectrometer with reference gases (e.g. CO2, CO, H2, O2, N2 or their mixtures with known relative abundances) with known flow rate. The method was tested using simple chemical compounds such as CaCO3, which give well-known amounts of pure gases during their thermal decomposition. We present initial QEGA data on two reference meteorites, Allende and Murchison. Our QEGA work is also informing the design and operation of ProSPA spaceflight instruments being developed to perform analogous experiments in situ on the lunar surface through the European Space Agency's PROSPECT payload on Luna 27. Highlights: The paper describes a quantitative evolve gas analysis with application to two meteorite samples. The method is based on calibration of the quadrupole mass spectrometer sensitivity with respect to different gases. The method was verified by analyses of pure chemical compounds decomposing into simple gases upon heating.